Recanalization following Endovascular treatment and imaging of PErfusion, Regional inFarction and atrophy to Understand Stroke Evolution—NA1 (REPERFUSE-NA1). Issue 3 (April 2020) - Tariq, Sana; Sah, Rani Gupta; Chan, Leona; Rajashekar, Deepthi; McTaggart, Ryan; Butcher, Kenneth; Aviv, Richard; Swartz, Rick; Field, Thalia; Tarpley, Jason; Shah, Ruchir; Hill, Michael; et al.
Rationale: Following endovascular treatment, poor clinical outcomes are more frequent if the initial infarct core or volume of irreversible brain damage is large. Clinical outcomes may be improved using neuroprotective agents that reduce stroke volume and improve recovery. Aim: The aim of the REPERFUSE NA1 was to replicate the preclinical neuroprotection study that significantly reduced infarct volume in a primate model of ischemia reperfusion. Specifically, REPERFUSE NA1 will determine if administration of the neuroprotectant NA1 prior to endovascular therapy can significantly reduce early (Day 2 subtract Day 1 diffusion-weighted imaging volume) and delayed secondary infarct (90-day whole brain atrophy plus FLAIR volume—Day 1 diffusion-weighted imaging volume) growth, as measured by magnetic resonance imaging. Methods and design: REPERFUSE-NA1 is a magnetic resonance imaging observational substudy of ESCAPE-NA1 (ClinicalTrialGov NCT02930018). A total of 150 acute stroke patients will be recruited (including 20% attrition) that have been randomized to either NA1 or placebo in the ESCAPE-NA1 trial. Study outcomes: Primary—Early infarct growth measured using diffusion-weighted imaging will be at least 30% smaller in patients receiving NA1 compared to placebo. Secondary—Delayed secondary stroke injury at 90 days will be significantly reduced in patients receiving NA1 compared to placebo, as well as delayed secondary growth at 90 days. Conclusion: REPERFUSE-NA1 will demonstrate the effect of NA1 neuroprotection on reducing the early and delayed stroke injury after reperfusion treatment.